1973
DOI: 10.1128/iai.8.5.743-751.1973
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Allescheria boydii for Mice

Abstract: Allescheria boydii and its imperfect state, Monosporium apiospermum, were studied to determine whether asexual or sexual strains might exhibit different pathogenic potentials for mice. Six different strains of the fungus were inoculated into mice by the intravenous, intracerebral, intraperitoneal, and intranasal routes. Cortisone-treated mice regularly developed infections after inoculation by any of the routes tested. Mice that had not been treated with cortisone were most susceptible to infection by the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…We isolated some of the fungi from soil (19a) and also used clinical specimens from our institute. Other isolates were graciously furnished by Libero Ajello, Mycology Division, Centers for Disease Control, Atlanta, Ga., Robert Samson, Centraalbureau voor Schimmelcultures, Baarn, Holland, and David Lupan (14), Department of Microbiology, University of Reno, Reno, Nev. All of the cultures were maintained in sterile water at room temperature in our culture collection.…”
Section: Materls and Methodsmentioning
confidence: 99%
“…We isolated some of the fungi from soil (19a) and also used clinical specimens from our institute. Other isolates were graciously furnished by Libero Ajello, Mycology Division, Centers for Disease Control, Atlanta, Ga., Robert Samson, Centraalbureau voor Schimmelcultures, Baarn, Holland, and David Lupan (14), Department of Microbiology, University of Reno, Reno, Nev. All of the cultures were maintained in sterile water at room temperature in our culture collection.…”
Section: Materls and Methodsmentioning
confidence: 99%
“…Michael Cazin's students at the University of Iowa (117). The pathogenicity of this fungus was found to be related to both the sexual and asexual forms (262).…”
Section: Scientificmentioning
confidence: 98%
“…Since these studies have been relatively unsuccessful, investigators have concluded that these fungi have little virulence for laboratory animals. On the other hand, our investigations of several isolates of P. boydii and M. apiospermum have shown that individual isolates are virulent for mice, although at considerably different 50% lethal doses (LD5o) (15). Mice were found consistently to be susceptible to a fulminating petriellidiosis when the intravenous route of infection was utilized.…”
mentioning
confidence: 99%
“…Partial characterization of some antigens has been described (16). The LD50 values for P. boydii strains 801, 807, and 809 and M. apiospermum strains 806, 813, and 815 for intravenously inoculated mice were 2.95 X 104, 19.1 X 104, 10.0 X 104, 1.29 x 104, 0.95 X 104, and 3.72 x 104 spores, respectively (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation